TYPES OF COMPOSITION AND MODERN GARDEN PARK - Isroilov G; Babadjanova L; Turdiev S.A. (Journals Park Publishing, 2022)
The article describes the use of landscape compositions by species and their biomorphological appearance in the construction of modern gardens in the form of landscape design, as well as data on building indicators, area and appearance of Singaporean gardens with an innovative look.
Keywords: Landscape; flowerbed; rabatka